Competence Of Cooperative Administrators: Cross-Sectional Survey of Cooperative Members in The Organizational Environment in The City of Bandung - Farid Riadi (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2021)
Competence is an essential part of completing the organization's tasks that need to be achieved by individuals in the organization. This study aims to determine the description of the competence of cooperative management. The researcher used a survey approach to find out the description of the competence of the cooperative management. Respondents in this study were 318 members of cooperatives in the organizational environment in the city of Bandung. The study results illustrate that the competence of the management is in the reasonably good category. However, there are still weak aspects that illustrate that the competencies of members and leaders do not fully have the expected competencies, such as behavior that reflects competence in the field of cooperatives, which is still very rarely found in members and also cooperative management apart from the way members think, and also leaders in determining actions for cooperatives felt to be still not fully optimized. Therefore, researchers recommend that efforts improve cooperative behavior within the leadership by appointing cooperative administrators who have the characteristics needed to lead cooperatives. Their outpouring of hearts, thoughts, and behavior can describe a strong character.